2010
DOI: 10.1016/j.jtcvs.2010.07.060
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Valsalva graft and long-term follow-up

Abstract: The reimplantation type of valve-sparing procedure can be facilitated by the use of the Valsalva graft and can be performed with satisfactory perioperative and midterm results. How an optimal root reconstruction will affect the second decade of follow-up has yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 22 publications
4
41
1
Order By: Relevance
“…Thus, adding the sinus structure to the semilunar valve root to enhance the semilunar valve function was believed to be reasonable. Among the adult population, it was common to use the "Valsalva graft" for valve-sparing aortic root replacement to preserve the spared aortic valve function [15]. However, the concerns of creating bulging sinuses on the valved ePTFE conduit for RVOT reconstruction have included its safety and efficacy.…”
Section: Commentmentioning
confidence: 99%
“…Thus, adding the sinus structure to the semilunar valve root to enhance the semilunar valve function was believed to be reasonable. Among the adult population, it was common to use the "Valsalva graft" for valve-sparing aortic root replacement to preserve the spared aortic valve function [15]. However, the concerns of creating bulging sinuses on the valved ePTFE conduit for RVOT reconstruction have included its safety and efficacy.…”
Section: Commentmentioning
confidence: 99%
“…Following remodeling, freedom from moderate or severe AI at 10 years was 64 % in the study by Yacoub et al, 25 96 % for bicuspid valves, and 87 % for tricuspid valves as reported by Aicher et al 26 Following reimplantation, freedom from reoperation at 10 years was 93 % for David et al 27 and 88 % for De Paulis et al 28 Aortic valve sparing operations have been shown to have good long-term outcomes in experienced centers and offer the ability to maintain the patient's native valve.…”
Section: Outcomes For Aortic Valve Repair and Valve Sparing Aortic Romentioning
confidence: 84%
“…31) De Paulis states that the rate of freedom from aortic valve reoperation at 10 years after VSRR using the Valsalva graft is 91%. 32) Urbanski described another novel technique in which each pathological sinus is excised and replaced with a teardrop-shaped patch. 33) Hess and colleagues developed the Florida sleeve, which is another less invasive approach.…”
Section: Various Vsrr Techniquesmentioning
confidence: 99%